Effect of gravity on visco-elastic surface waves in solids involving time rate of strain and stress of higher order. (1995) - Das, Tapan Kumar; Sengupta, P. R.; Debnath, Lokenath
Abstract : A study is made of the surface waves in a higher order visco-elastic solid involving time rate of change of strain and stress under the influence of gravity. A fairly general equation for the wave velocity is derived. This equation is used to examine various kinds of surface waves including Rayleigh waves, Love waves and Stoneley waves. It is shown that the corresponding classical results follow from this analysis in the absence of gravity and viscosity.